Biphasic Roles of Hedgehog Signaling in the Production and Self-Renewal of Outer Radial Glia in the Ferret Cerebral Cortex. (18th May 2021) - Hou, Shirui; Ho, Wan-Ling; Wang, Lei; Kuo, Bryan; Park, Jun Young; Han, Young-Goo
Abstract: The neocortex, the center for higher brain function, emerged in mammals and expanded in the course of evolution. The expansion of outer radial glia (oRGs) and intermediate progenitor cells (IPCs) plays key roles in the expansion and consequential folding of the neocortex. Therefore, understanding the mechanisms of oRG and IPC expansion is important for understanding neocortical development and evolution. By using mice and human cerebral organoids, we previously revealed that hedgehog (HH) signaling expands oRGs and IPCs. Nevertheless, it remained to be determined whether HH signaling expanded oRGs and IPCs in vivo in gyrencephalic species, in which oRGs and IPCs are naturally expanded. Here, we show that HH signaling is necessary and sufficient to expand oRGs and IPCs in ferrets, a gyrencephalic species, through conserved cellular mechanisms. HH signaling increases oRG-producing division modes of ventricular radial glia (vRGs), oRG self-renewal, and IPC proliferation. Notably, HH signaling affects vRG division modes only in an early restricted phase before superficial-layer neuron production peaks. Beyond this restricted phase, HH signaling promotes oRG self-renewal. Thus, HH signaling expands oRGs and IPCs in two distinct but continuous phases during cortical development.